Corticotrophin-Releasing Factor Modulates Cerebellar Purkinje Cells Simple Spike Activity in Vivo in Mice - Wang, Hong-Wei; Zhao, Jing-Tong; Li, Bing-Xue; Su, Shan-Shan; Bing, Yan-Hua; Chu, Chun-Ping; Wang, Wei-Ming; Li, Yu-Zi; Qiu, De-Lai (Frontiers in Cellular Neuroscience, 2018)
Corticotropin-releasing factor (CRF) is a major neuromodulator that modulates cerebellar neuronal activity via CRF receptors during stress responses. In the cerebellar cortex, CRF dose-dependently increases the simple spike (SS) firing rate of Purkinje cells (PCs), while the synaptic mechanisms of this are still unclear. We here investigated the effect of CRF on the spontaneous SS activity of cerebellar PCs in urethane-anesthetized mice by in vivo electrophysiological recording and pharmacological methods. Cell-attached recordings from PCs showed that micro-application of CRF in cerebellar cortical molecular layer induced a dose-dependent increase in SS firing rate in the absence of GABAA receptor activity. The CRF-induced increase in SS firing rate was completely blocked by a nonselective CRF receptor antagonist, α-helical CRF-(9-14). Nevertheless, application of either a selective CRF-R1 antagonist, BMS-763534 (BMS, 200 nM) or a selective CRF-R2 antagonist, antisauvagine-30 (200 nM) significantly attenuated, but failed to abolished the CRF-induced increase in PCs SS firing rate. In vivo whole-cell patch-clamp recordings from PCs showed that molecular layer application of CRF significantly increased the frequency, but not amplitude, of miniature postsynaptic currents (mEPSCs). The CRF-induced increase in the frequency of mEPSCs was abolished by a CRF-R2 antagonist, as well as protein kinase A (PKA) inhibitors. These results suggested that CRF acted on presynaptic CRF-R2 of cerebellar PCs resulting in an increase of glutamate release through PKA signaling pathway, which contributed to modulation of the cerebellar PCs outputs in vivo in mice.